Automatic Referral to Standardize Palliative Care Access: An International Delphi Survey - Hui, David (Support Care Cancer, 2017)
PURPOSE: Palliative care referral is primarily based on clinician judgement, resulting in highly variable access. Standardized criteria to trigger automatic referral have been proposed, but it remains unclear how best to apply them in practice. We conducted a Delphi study of international experts to identify a consensus for the use of standardized criteria to trigger automatic referral. METHODS: 60 international experts stated their level of agreement for 14 statements regarding the use of clinician-based referral and automatic referral over 2 Delphi rounds. A consensus was defined as an agreement of ≥70% a priori. RESULTS: The response rate was 59/60 (98%) for the first round and 56/60 (93%) for the second round. 26 (43%), 19 (32%) and 11 (18%) respondents were from North America, Asia/Australia and Europe, respectively. The panel reached consensus that outpatient palliative care referral should be based on both automatic referral and clinician-based referral (agreement=86%). Only 18% felt that referral should be clinician-based alone, and only 7% agreed that referral should be based on automatic referral only. There was consensus that automatic referral criteria may increase the number of referrals (agreement=98%), facilitate earlier palliative care access and help administrators to set benchmarks for quality improvement (agreement=86%). CONCLUSIONS: Our panelists favored the combination of automatic referral to augment clinician-based referral. This integrated referral framework may inform policy and program development.